Strategiya Olimiiskoi podgotovki - Rubin, V. S. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The long term (four-year) conception of training and preparation of athletes toward Olympic games - key points, main tasks, startegic important points, problems ...) is presented.